Assessment of Notch Effect Based on Finite Element Analysis and Digital Image Correlation Technique. Issue 2 (19th October 2020) - Kumar, Abhay; Chaitanya, Gudibanda Maruthi Sri Krishna; Goyal, Sunil; Goswami, Mohit; Kumar, Anish; Ul Harmain, Ghulam Ashraf
Abstract : Triaxial state of stress experienced by structural components due to complex geometry, discontinuities, or type of loading can be studied by tensile testing of notched specimens. Herein, assessment of tensile deformation of 316LN austenitic stainless under the uniaxial and triaxial stresses is presented based on finite element (FE) analysis and digital image correlation (DIC). To study their effects, notches of different root radii are incorporated in flat smooth specimens. The strength of the material increases in the presence of notch. Among the various constitutive expressions, the Swift equation provides a better representation of the tensile response for the smooth specimen. The analysis is further extended by incorporating Swift equation parameters as the deformation model in the FE analysis for notched specimens. The tensile response of the notched specimens is predicted well using the FE analysis. The in‐house algorithm is developed for DIC and used to estimate the strain in smooth and notched specimens by speckle‐pattern image analysis. The total displacement of smooth and notched specimens obtained from the FE analysis and DIC technique is comparable to the experimental results. Both the techniques complemented each other in understanding the deformation behavior of the steel. Abstract : Notch tensile behavior of 316LN SS is studied using finite element (FE) analysis and digital image correlation (DIC) technique. The complete elasto‐plastic response of notched specimens is predicted well using FE analysis. The in‐house DIC algorithm predicts the onset of triaxiality and strain localization accurately during deformation. The total displacement is comparable by FE analysis and DIC for all specimens.